Classification of five kinds of moss plants with the use of Fourier transform infrared spectroscopy and chemometrics. Issue 6 (2011) - Hu Hu, Tao Tao; Jin Jin, Wen-Ying Wen-Ying; Cheng Cheng, Cun-Gui Cun-Gui
Abstract : Fourier transform infrared spectroscopy (FT-IR) with Horizontal Attenuated Total Reflectance (HATR) techniques is used to obtain the FT-IR spectra of five kinds of mosses, such as Ptychomitrium dentatum (Mitt.) Jaeg., Ptychomitrium polyphylloides (C. Muell.) Par., Ptychomitrium sinense (Mitt.) Jaeg., Macromitrium syntrichophyllum Ther. Etp. Vard., and Macromitrium ferriei Card. Sz Ther. Based on the comparison of the above mosses in the FT-IR spectra, the region ranging from 4000 to 650 cm −1 was selected as the characteristic spectra for analysis. Principal component analysis (PCA) and cluster analysis are considered to identify the five moss species. Because they belong to the homogeneous plants, and have similar chemical components and close FT-IR spectroscopy, PCA and cluster analysis can only give a rough result of classification among the five moss species, Fourier self-deconvolution (FSD) and discrete wavelet transform (DWT) methods are used to enhance the differences between them. We use these methods for further study. Results show that it is an excellent method to use FT-IR spectroscopy combined with FSD and DWT to classify the different species in the same family. FT-IR spectroscopy combined with chemometrics, such as FSD and DWT, can be used as an effective tool in systematic research of bryophytes.